'Pasi nemakomoredzi—ii!' [Down with comrades!]: ZANLA guerrilla fighters – civilian relations in Gudyanga, Melsetter, Rhodesia, 1975–1980. Issue 2 (4th May 2019) - Chimhete, Nathaniel
Abstract : The paper examines the relationship between Zimbabwe African National Union (ZANU) guerrilla fighters and civilians in the Gudyanga area, Chimanimani West, from 1975 to 1980. It focuses on how the residents of that area interacted with guerrilla fighters during the war of liberation. In examining the relationship between civilians and guerrilla fighters, the paper follows in the footsteps of scholars, such as Norma Kriger, who emphasize the agency of peasant communities. It, however, goes beyond Kriger's work by paying particular attention to Gudyanya residents' discursive forms of engagement with guerrilla fighters. It argues that scholars' failure to consider discursive forms of engagement led them to not fully appreciate the agency of rural communities in their interaction with freedom fighters. These discursive forms of engagement manifested themselves in songs that mocked guerrilla fighters, in nicknames given to freedom fighters, and in the names families gave to children born out of guerrilla fighters' relationships with local women.